THE SOUTH AFRICAN FIELD POST AND TELEGRAPH CORPS (1914-1915) - Ploeger, Jan (Scientia Militaria - South African Journal of Military Studies, 2012)
a. Before the formation of the Union Three hundred and seventy years separate the reader from 7th July, 1501, the day on which the Portuguese mariner Joao de Nova, landed at Mosselbay to place a letter in an old shoe in the hope that one of his countrymen would visit the "Post Office Tree" and would find and read this - the oldest known postal article of our country's history.